Myth of explosion prevention configuration in hazardous area - Yeong, Chin Hao (2022)
Explosion preventions play a very important role in all kinds industry in this modern world, especially in the oil & gas industry. An explosion can cause major damage to the building and loss of human life. Recently there was a huge explosion that happened in Lebanon Beirut cause hundreds of death and a lot of property and building was damaged and an estimated few hundred thousand people were homeless due to a large amount of ammonium nitrate without proper storage and safety measurement. Therefore, explosion prevention is very important no matter in what kind of industry. With the correct method of prevention explosion in the hazardous area, it may reduce the percentage of the explosion incident that happen and by applying this in the industry it may save a lot of life and cost. Explosion prevention or protection shall accordance with the IEC 60079 standard to design or install the equipment in the hazardous area. Unfortunately, human is the main cause of making mistake during the design stage or installation of equipment in hazardous area which is not according to the IEC 60079 standard. The main objective of this research is to enhance the method and use the suitable method to prevent the explosion in the hazardous area. Besides that, also reduce the mistake and error made by a human during design and installation. Based on the case study and IEC standard model an electronic field device such as an Intrinsic safety barrier and compare with energy curve. Based on the case study and calculation to identify the suitable protection method to avoid the explosion. The expected outcomes of this research, based on the analysis we can identify the reliability of the electronic device which suitable to operate in the hazardous area and reduce the engineering and operation cost.